SPORTS NUTRITION: CHARACTERISTICS, CURRENT RESEARCH STATUS AND AREAS OF PATENTING OF INVENTIONS AND UTILITY MODELS - R, Shegelman I.; M., Kirilina V.; L. E., Blazhevich; O. E, Smirnova; A. S, Vasilev (International Journal of Psychosocial Rehabilitation, 2020)
This article presents the research that indicated the growing interest in Russia to healthy lifestyle and healthy functional nutrition, including sports nutrition. Meanwhile, despite the serious scientific research taking place in Russia, imported food products prevail on the markets of sports nutrition, while Russian producers of such production are poorly introduced on the foreign markets. Russian researchers, developers and producers of sport food products do not pay enough attention to the production of patentable intellectual property objects and protection of results of their intellectual activity. It follows from the above, this article presents the analysis of the Russia’s current state of the research, characteristics and areas of development of new intellectual properties objects related to functional sports nutrition.